The Role of Social Capital in the Employability of University Graduates in Zambia: A Case of University of Zambia Graduates - Machacha, Eliphas (European Scientific Journal, ESJ, 2021)
The research presented in this paper was designed to investigate the role of social capital in the employability of University Graduates in Zambia: A Case of University of Zambia Graduates. The study focused on the period between the years 2000 and 2015. In this study social capital was operationalised as social connections that can be used in search of jobs. Employability was operationalised as the ability to get employed or get a job. This research used a sequential mixed method research design to investigate the research problem. The study was carried out in the City of Lusaka. 208 University of Zambia Graduates and 16 employers participated in this study. Data were collected using a questionnaire and interviews. Statistical Package for Social Sciences (SPSS) was used in the management and analysis of quantitative data while thematic analysis was applied in the analysis of qualitative data. The results from this study indicated that UNZA Graduates attach a lot of importance to the use of social connections in search of job opportunities in the labour market. However, only powerful social connections were effective in this process and were not available to everyone. The results also revealed that social connections through relatives and close friends were more effective in their employability than social connections through acquaintances and potential employers. In conclusion, this study showed that social connections facilitated by relatives and close friends through people of influence in society were more effective but, to a large extent, they depend on one’s social status.